Effect of Air Pressure on Changes in Parameters and Soil Settlement Behavior in Very Soft Soils - Sutarman, Encu; Wardani, Sri Prabandiyani Retno; Muntohar, Agus Setyo (Civil Engineering Journal, 2025)
An effective soil improvement method is essential in soft soil due to the poor bearing capacity for construction loads. To address the challenge, the use of the staged air pressure method with Suction Assisted Vacuum Preloading (SAVP) has shown significant potential when applied through Geosystem Air Booster Vacuum Preloading (GAVP), specifically designed with a sensor system as a real-time measuring tool for soil parameter changes. Therefore, this research aims to examine the effectiveness of the SAVP method in relation to the discharge of drained water from prefabricated vertical drains (PVD) on changes in soil parameters due to air pressure and vacuum using the GAVP tool. The method used five PVDs in large-diameter soil sample tubes, applying air pressure and vacuum simultaneously and selectively. This experimental setup was designed to examine the fundamental aspects of soil parameter changes, namely permeability, consolidation, and volume compression coefficient. The results showed that soil parameters during testing interacted with each other, where air pressure balanced with vacuum caused changes and optimized settlement and consolidation efficiency. Decreasing air pressure enhanced vacuum performance, causing a corresponding rise in soil settlement and consolidation degree. However, increasing air pressure decreased soil settlement and the degree of consolidation.